Intelligence Quotient (IQ) in school-aged preterm infants: A systematic review - Lacalle, Laura; Martínez-Shaw, Melissa Liher; Marín, Yolanda; Sánchez-Sandoval, Yolanda (Frontiers in Psychology, 2023)
Preterm birth (before 37 weeks of gestational age) is associated with certain risks to child development. The aim of this systematic review was to summarize available and updated empirical evidence on prematurity as a risk factor for cognitive development in school age. Thus, we attempted to identify similarities and differences with the full-term population and to point out possible risk or protective factors among the biological, psychosocial and family variables. The conceptualization and methodology of this review followed the PRISMA recommendations. The search was carried out in Web of Science, Scopus, PsycInfo, and Dialnet databases, in May 2022. The search was limited to journal articles, published between 2012 and 2022, in English and Spanish. Research articles selected were those focused on the intelligence quotient (IQ) of preterm children aged 6–12 years. The review included studies with cross-sectional or longitudinal cohorts, compared to a control group of children born at term or to standardized scales. The quality of evidence of the selected studies was verified with the Mixed Methods Appraisal Tool (MMAT). The initial search identified 1,040 articles. Forty articles met the inclusion criteria and were finally included in this review. These studies involved 5,396 preterm children from 37 different cohorts. Despite the diversity found among the results, in general, total IQ scores were within the normative mean for premature children; however, compared to their full-term peers, these scores were lower. The most studied variables in relation to IQ are perinatal (e.g., gestational age and birth weight) and family (e.g., socioeconomic level and education level of the mother). Recent studies corroborate that premature birth affects cognitive development in school age, and identify associated perinatal and family variables. Systematic review registration https://www.crd.york.ac.uk/PROSPERO/display_record.php?RecordID=337371; identifier: CRD42022337371.